Logical Positivism and the Challenge of Epistemic Claims - Ade-Ali, Funmilayo Arinola (NIU Journal of Humanities, 2019)
Before Hume, there was empiricism as developed by John Locke and Berkeley. But they all failed to draw empiricism to its logical conclusion. For both Locke and Berkeley, ideas exist in the mind and they are the only things that exist. With the emergence of Hume, empiricism as an intellectual doctrine becomes broaden. He reforms empiricism and asserts that, there could be no ideas without antecedent impressions. Logical Positivism as a philosophical school of thought is best defined as a general attitude of the mind, a spirit of inquiry, an approach to the facts of human existence. In this connection, logical positivism as an analytic philosophy engages in re-constructing empiricist criteria and approach for analyzing epistemic claims. Hence, the attempt to establish in this paper, the logical positivist challenge on the existing empiricist claims with a view of illustrating how logical positivism has lifted the epistemic claims beyond the scope of Lockean and Berkeleyean philosophy using cognitive verifiable principle that has link with the external world. Keywords: Empiricism, Logical Positivism, Mind, Epistemic, Cognitive.